Evaluation of Impulse Unloading Efficiency Pertaining to APS Power Block Turbine for Higher Dynamic Steadiness - Yu. D. Filipchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers the influence of impulse unloading of APS power block turbine on its dynamic steadiness. The performed calculations while simulating four various impulse turbine characteristics have shown that the highest effect is obtained while characteristics of APS power block turbine are close to the characteristics of a steam turbine K-300/240. It has been established that an application of standard time interval for emergency automation startup and existing delay in the operation of electro-hydraulic transformer do not allow to influence on acceleration area and the positive effect due to load shedding is reached only due to an increase of braking site. While decreasing time period for control signal supply from 0,2 sec to 0,1 sec it is possible to increase steadiness by 10 %  for impulse characteristics of APS power blocks and by 39,9–42,6 % – for characteristics of the turbine K-300/240.